The social construction of migrant care work. At the intersection of care, migration and gender - King Dejardin, Amelita (Geneva, 2019)
"This publication examines the implications of migration in the care economy and its effects on women’s economic empowerment and gender equality. It focuses on the working conditions of women and men migrants performing care work in destination countries; how migration in the care economy affects gender equality at work; and areas for policy action. The paper highlights the need for effective and coordinated policies to help improve the governance of labour migration for health-care workers, address decent work deficits of care workers for better recruitment and retention and improve skills recognition and certification."